Reading Habits and Their Influence on Student English Writing Skill in Indonesia: A Systematic Review - Fadli Zam Zami; Haniful Umam; Mutmainnah Mustofa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This systematic review investigates the influence of reading habits on the writing skills of Indonesian EFL (English as a Foreign Language) students, based on 24 selected articles from a pool of 30 Scopes-indexed studies from 2014-2024. The findings reveal a clear connection between regular reading habits and enhanced writing proficiency, particularly in grammar, creative thinking, and content organization. However, challenges such as limited exposure to English, inadequate meta-cognitive strategies, and a lack of reading culture hinder progress. Technological integration can mitigate these barriers and foster reading and writing development if effectively implemented. The study highlights strategies to promote reading habits, including using multimedia tools, encouraging independent learning, developing meta-cognitive strategies, and fostering international collaboration in academic research. By addressing these areas, educational practices in Indonesia can more effectively support EFL learners in improving their English writing skills through enhanced reading engagement.